The achievement of minimum service standards performance indicators at the Sungai Duren Community Health Center in Muaro Jambi Regency - Amir, Andy; Mekarisce, Arnild Augina; Asparian; Syamsurizal (Proceedings Academic Universitas Jambi, 2025)
Background: The urgency of this study lies in the fact that the implementation of Minimum Service Standards at the Sungai Duren Community Health Center is still not optimal, with only three indicators showing improvement: health services for toddlers, health services for people with mental disorders, and HIV health services. It is important to improve and optimize minimum health service standards in accordance with the target of 100% achievement. Objective: The purpose of this study was to analyze of the achievement of minimum service standard performance indicators at the Sungai Duren Community Health Center. Methods: This research method is qualitative research with an analyse approach based on four approaches, namely analyze of input, process, and output. Results: The implementation of Minimum Service Standards at the Sungai Duren Community Health Center is still not optimal, with only three indicators showing improvement. The lowest achievements were recorded in health services for toddlers at 40.03% and productive age at 43.26%. Several factors that hindered the health center included limited human resources, facilities and infrastructure, a monitoring system that was not yet running optimally, and suboptimal service management and community participation. Conclusion: It is hoped that there will be increased collaboration between health workers and relevant stakeholders in achieving the highest possible minimum health service standards in a more optimal and intensive manner to make the community the subject of health, not just the object of health, by involving the community in the planning, implementation, monitoring, and evaluation stages within the scope of health efforts.